Chromatographic profiling of secondary metabolites in pandanus amaryllifolius via high performance liquid chromatography (HPLC) / Abdul Rasyid Zulkifli - Zulkifli, Abdul Rasyid (2015)
Secondary metabolites in plants have numerous medicinal properties which are health beneficial. These secondary metabolites can be found in a variety of plants around the world including the Pandanus species. Pandanus amaryllifolius is well known in the South East Asia countries such as Malaysia, Indonesia and Thailand. In Malaysia, the leaves are commonly used as a flavouring and colouring agent in dishes by the locals. However, few information are available about the usage of the secondary metabolites containing in the Pandanus amaryllifolius leaves. Therefore, this study was conducted to obtain the chromatographic profile of secondary metabolites in Pandanus amaryllifolius. The leaf sample was extracted with methanol and subjected to the reverse-phase HPLC for separation with water and acetonitrile as the mobile phase. Gradient elution was conducted and the separation was observed by using diode array detector at )., = 220 - 260 nm and analysed via ChemStation B.01.01 Sri. The chromatograms had shown significant peaks which could indicate the presence of secondary metabolites, but was unable to be identified as there were absence of standards. Upon comparison, the best chromatographic profile was shown by the sample obtained from Bandar Utama, Kuala Lumpur.